PERCEPTION OF THE EKAS BUANA COASTAL COMMUNITY TOWARDS THE LARGE-SCALE SEAWEED INDUSTRY DOWNSTREAM MODELING PROJECT - Junaidi, Junaidi; Ashari, Ria (Universitas Mataram, 2025)
The large-scale seaweed industry downstream modeling project on the coast of Ekas Buana village, East Lombok district, has been made a national strategic project by the central government. The potential of natural resources owned by the Ekas Buana coast has made policy makers from the center to stakeholders at the regional level utilize the coastal area optimally and complexly with a relatively narrow area. The purpose of the study was to determine the perception of the Ekas Buana community towards the large-scale seaweed industry downstream modeling project. The data collection method used a questionnaire. Data was reduced using a Likert scale and simple statistics and to obtain conclusions were described qualitatively descriptively. The results of the study obtained the perception of the community of cultivators towards the large-scale seaweed industry downstream project in the categories of know, agree, and positive, a percentage score of 33.4% was obtained, and in the category of Don't Know, Disagree, Not Positive a percentage score of 35.8% was obtained, and in the category of Very Don't Know, Very Disagree, Very Not Positive a percentage score of 17.6% was obtained, meaning that these three categories still dominate the perception of the unexpected category, namely a score higher than the most expected score. The perception of the community from the government, business elements and community leaders was dominated by a good perception, where the respondents' answers were dominated by the most expected answer, namely 43.56%.The conclusion of this study is that the perception of the Ekas Buana community towards the large-scale seaweed industry downstream project is dominated by people who have a negative perception, disagree, and don't know. Keywords: perception; industrial down streaming; seaweed.